LAMA PEMBEKUAN DARAH MENGGUNAKAN SPONGOSTAN DAN ALVOGYL PADA PASIEN POST ODONTECTOMY GIGI MOLAR TIGA BAWAH DI RUMAH SAKIT - Ridwan Sri Haryono; Suharjono Suharjono; Siti Hidayati (Journal of Oral Health Care, 2014)
Background:Tooth with hearing lies one seed will cause abnormalitiesin the eruption, one of which is impaction occurs.Mandibular third molar impaction can interfere with masticatoryfunction and often leads to various complications. Bleedingis one of the events that can occur in patients post odontectomy.Materials commonly used after revocation actionsand odontectomy is spongostan and alvogyl. Objective:To determinethe difference between use and alvogyl spongostanthe patient’s blood clotting time post odontectomy lower thirdmolars.Methods:This research uses experimental methodsto study design pre Static Group Comparison. The populationin this study were patients post odontectomy third molarsunder 30 people with the following criteria: (1) Teeth are deprivedof the mandibular third molars right or left grade 1 ; (2)Male or female, (3) Age 20 -50 years, (4) Do not have a systemicdisease. The technique of sampling using random samplingor random. Analysis of the data used in this research isusing independent t - test test. This study was conducted inAugust – Oktober 2013 in the RS JIH Yogyakarta Jln. RingRoad utara No 160 Yogyakarta.Results:The test results peiredt -test on blood clotting time difference post odontectomy afteradministration alvogyl spongostan and obtained values of0.000 significancy (P<0.05). Conclusion:There is a differencebetween use and alvogyl spongostan the patient’s blood clottingtime post odontectomy lower third molars.